Mengapa Program Linear Penting Untuk Pengambilan Keputusan Bisnis - mutiara sapriani; Anggi Dola Putri; Zariah Sakinah; Tasya Widianto Rizky; Amin Harahap (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
In an increasingly competitive business environment, organizations are required to make accurate and efficient decisions based on limited resources. Linear programming is a mathematical optimization technique that plays a crucial role in supporting managerial decision-making processes. This method enables businesses to determine the optimal allocation of resources such as labor, capital, and materials in order to maximize profit or minimize costs while considering various operational constraints. This study aims to examine the importance of linear programming in business decision-making and to analyze its impact on operational efficiency and profitability. The research employs a qualitative descriptive approach by reviewing relevant literature, business case studies, and empirical findings related to the application of linear programming models. The results indicate that linear programming significantly improves decision accuracy, reduces operational costs, and enhances productivity across different business sectors, including manufacturing, logistics, finance, and marketing. Furthermore, the findings reveal that companies implementing linear programming models are better equipped to manage complex decision scenarios, forecast outcomes, and adapt to dynamic market conditions. Therefore, linear programming is not only a valuable analytical tool but also a strategic instrument that contributes to sustainable business growth.